The NETLAKE Metadatabase—A Tool to Support Automatic Monitoring on Lakes in Europe and Beyond. (27th October 2017) - Jennings, Eleanor; de Eyto, Elvira; Laas, Alo; Pierson, Don; Mircheva, Georgina; Naumoski, Andreja; Clarke, Andrew; Healy, Michael; Šumberová, Kateřina; Langenhaun, Daniel
Abstract: Sharing data is a keystone of collaborative science. A fundamental barrier, however, can be a lack of knowledge on what is being collected, where, and by whom. The aim of NETLAKE (COST Action ES1201) was to build a network of sites and individuals to support development and deployment of automatic sensor‐based systems on lakes and reservoirs in Europe. To support this, NETLAKE developed a metadatabase which could provide answers to questions on where lakes were monitored, details on the frequency and duration of monitoring, contact details, and which sensors were being used. Development included challenges related to time and resources, and indeed to communication between lake scientists and database experts. In total, metadata for 71 European lakes were captured. The resulting data revealed interesting facts; for example, seven sites had archives that spanned over a decade, only seven of these lakes were used as drinking water sources, and one was a large fish pond. GLEON, the Global Lake Ecological Observatory Network, and two pan‐American projects are now adding their metadata and the metadatabase is developing into a tool for the global community which can promote high frequency monitoring and facilitate network science.